2021
DOI: 10.1159/000516811
|View full text |Cite
|
Sign up to set email alerts
|

Natural Course and Prognostic Factors of Immediate-Type Peanut Allergy in Children

Abstract: <b><i>Background:</i></b> Predicting food allergy resolution is essential to minimize the number of restricted foods in children. However, there have been no studies on the natural history of peanut allergy (PA) in Korea. <b><i>Objective:</i></b> This study aimed to evaluate the natural course and prognostic factors of immediate-type PA in children till the age of 10 years. <b><i>Methods:</i></b> We retrospectively collected data of 122 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Peanut and tree nut allergies are more durable than egg and milk allergies. Depending on the study population, peanut allergy resolved in 14.8% to 29% by ages 6 through 10 years, and tree nut allergy resolved in 9% by a median age of 10 years (range, 5.8-15.7 years) …”
Section: Epidemiology Common Food Allergens and Natural Historymentioning
confidence: 99%
“…Peanut and tree nut allergies are more durable than egg and milk allergies. Depending on the study population, peanut allergy resolved in 14.8% to 29% by ages 6 through 10 years, and tree nut allergy resolved in 9% by a median age of 10 years (range, 5.8-15.7 years) …”
Section: Epidemiology Common Food Allergens and Natural Historymentioning
confidence: 99%
“…Gupta et al found the prevalence of peanut allergy in early childhood, adolescence (14–17 years) and adulthood to be 2.6%, 2.1%, and 1.8%, respectively [ 2 •, 79 , 83 ]. Risk factors for peanut allergy persistence include diagnosis of atopic dermatitis at age one, sensitization to at least one tree nut/one other food/or dust mite, a low threshold for peanut reaction during an oral food challenge at age one [ 18 ••], peanut-specific IgE (sIgE) ≥ 1 kU/L at diagnosis [ 84 ], and anaphylaxis as initial reaction [ 85 ]. Having at least one Asian parent was a risk factor in both persisting egg and peanut allergy in the Australian HealthNuts study [ 11 ].…”
Section: Adolescencementioning
confidence: 99%
“…As reported by the same research team, the rate of resolution of peanut allergy by the age of 4 years was reportedly 22% in 2015 [ 29 ]. A retrospective analysis conducted at 3 hospitals in Korea reported that the probabilities of peanut allergy resolution were 10.3% at age 6 years and 32.8% at age 10 years [ 39 ].…”
Section: Natural Course Of Specific Food Allergiesmentioning
confidence: 99%
“…29) A retrospec tive analysis conducted at 3 hospitals in Korea reported that the probabilities of peanut allergy resolution were 10.3% at age 6 years and 32.8% at age 10 years. 39) Tree nut allergy accounts for a considerable proportion of food allergies in children and frequently cause severe reactions, but the natural course of tree nut allergy compared to other major food allergies remains understudied. 40,41) A study published in 2005 that is still consistently cited when referring to the natural course of tree nuts reported a resolution rate of 8.9% among children with previous clinical reactivity and evidence of tree nut sensiti zation.…”
Section: Longitudinal Cohort Canadamentioning
confidence: 99%